Thermo-responsive PNIPAM-metal hybrids: an efficient nanocatalyst for the reduction of 4-nitrophenol - Satapathy, Smith Sagar; Bhol, Prachi; Chakkarambath, Aswathy; Mohanta, Jagdeep; Samantaray, Kunal; Bhat, Suresh K.; Panda, Subhendu K.; Mohanty, Priti S.; Si, Satyabrata (Applied Surface Science, 2017)
Micron size thermoresponsive cross-linked polymeric microgels of poly(N-isopropylacrylamide) (PNIPAM) are used as "microreactor" for embedding metal nanoparticles of different shapes. Using a simple and robust method, we have synthesized various polymer-metal hybrid nanostructures incorporated with Au nanorods (AuNR), Au nanospheres (AuNS) and Ag nanospheres (AgNS). These hybrid nanostructures have been characterized by transmission electron microscope (TEM), UV-vis spectroscopy, dynamic light scattering (DLS) and static light scattering (SLS) followed by their catalytic activity. TEM studies directly confirmed the mondispersity of synthesized hybrid microgels and stability of the embedded metal nanoparticles within the microgels. Optical studies confirmed the presence of respective absorption bands that correspond to AuNS, AgNS and AuNR respectively. Extensive DLS studies demonstrated that although these hybrid microgels preserve their thermoresponsive properties, i.e their hydrodynamic radius decreased with increasing temperature, their thermosensitivity were comparatively lesser than pure PNIPAM microgels. Combining with studies using static light scattering, we further found that AuNS and AgNS were inhomogeneously distributed within microgels where the majority of the nanoparticles present within the loosely cross-linked shell. On the other hand AuNR were distributed more homogeneously within the microgels. Catalytic performance of various nanostructures loaded onto PNIPAM microgel beads were evaluated by studying the catalytic reduction of 4-nitrophenol. Complete catalytic conversion using AgNS occurred in similar to 30 min with a first-order rate constant of 0.159 min(-1) having a 7 min induction period. On the other hand no induction period was observed for AuNS and AuNR and the reaction completed in 3-4 min with a first-order rate constant of 1.607 min(-1) and 1.627 min(-1) respectively. Further, PNIPAM-AuNS and PNIPAM-AuNR possess better catalytic activity as well as recyclability compared to that of PNIPAM-AgNS. (C) 2017 Elsevier B.V. All rights reserved.